Mesenchymal stem cell-based therapy for female stress urinary incontinence - Liu, Xiaochun; Li, Tingting; Zhang, Jia; Lin, Xiling; Wang, Wenzhen; Fan, Xiaodong; Wang, Lili (Frontiers in Cell and Developmental Biology, 2023)
Stress urinary incontinence (SUI) diminishes the quality of life of patients, and not all patients can benefit from the currently available surgical and nonsurgical therapies. Mesenchymal stem cell (MSC)-based therapy has garnered increasing interest for regaining the ability to control urination. We reviewed the literature and analyzed recent studies dedicated to MSC-based therapies for SUI, summarized the recent treatment strategies and their underlying function mechanisms, while assessing their safety, effectiveness, and future prospects. In addition, we traced and sorted the root literature and, from an experimental design perspective, divided the obtained results into four categories: single MSC type therapy for SUI, MSC-based combination therapy for SUI, treatment of SUI with the MSC secretome, and other factors influencing MSC therapy. While evidence indicates that these treatment strategies are safe and effective, it is still necessary to better understand the underlying mechanisms of action and to conduct more clinical trials. Future studies should focus on designing clinical trials of MSC-based therapies, that is, determine the indications for their application, dosage of cells, appropriate surgical strategies, optimal cell sources; develop clinically relevant animal models; and make progress in understanding the molecular mechanisms of SUI improvements induced by stem cell therapies.